Surface cubic phase-rich functional modified hard alloy and preparation method thereof
By doping tungsten carbide with yttrium doping treatment and using boron-containing titanium carbide and cobalt-molybdenum composite powder, combined with nitriding sintering technology, the hardness and thermal conductivity of surface-rich cubic phase modified carbide is solved. The problem of high friction coefficient achieves increased hardness and reduced friction coefficient, and extends the service life of tool materials.
Patent Information
- Application Number
- CN202411795156.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing surface-rich cubic phase modified carbide has low Vickers hardness, insufficient thermal conductivity, and excessive friction coefficient, resulting in poor wear resistance.
By yttrium doping treatment of tungsten carbide, combined with the use of boron-containing titanium carbide and cobalt-molybdenum composite powder, and combined with the nitriding sintering process, the microstructure of the alloy is regulated to form a surface cubic phase-rich functionally modified carbide.
The Vickers hardness and thermal conductivity of cemented carbides are significantly improved, while the friction coefficient is reduced, and the wear resistance and service life of the material are improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cemented carbide tool materials, and in particular relates to a surface cubic-rich phase functionally modified cemented carbide and a preparation method thereof. Background Art
[0002] Cemented carbide is a metal-based high-hardness and wear-resistant composite material made by powder metallurgy with refractory metal carbides and nitrides as hard phases and metal as bonding phase, and also includes metal ceramic materials; the hard phase has the advantages of high hardness, high melting point and high thermal stability, while the tough metal bonding phase provides good ductility, toughness and excellent wettability. Surface rich cubic phase gradient cemented carbide is an alloy with a surface rich in nitride / carbonitride cubic phase. In a nitrogen atmosphere, nitrogen atoms gradually diffuse from the surface of the alloy to the inside. Due to the high nitrogen potential on the surface, other atoms gradually migrate to the surface of the alloy through the bonding phase due to the effect of thermal coupling, and combine with nitrogen atoms to form cubic nitrogen / carbonitride compounds, thereby forming a surface rich cubic phase gradient structure.
[0003] A Chinese patent (publication number CN114941097B) discloses a method for preparing surface cubic phase-rich gradient structure cemented carbide by denitrification process. By adding appropriate amount of ZrC and HfC cubic phase powder to the traditional gradient cemented carbide composition, controlling the alloy composition to be in cubic phase spinodal decomposition, and using denitrification gradient sintering, a gradient cemented carbide with a thin and smooth surface layer rich in cubic phase and an inner layer rich in binding phase and lacking cubic phase can be prepared. However, this patented technology does not solve the problems of low Vickers hardness, insufficient thermal conductivity, and poor wear resistance caused by excessively high friction coefficient of surface cubic phase-rich modified cemented carbide in the prior art, which seriously affects its practical application.
[0004] Therefore, how to modify the components of cemented carbide, combine it with nitriding and sintering process, improve the Vickers hardness and thermal conductivity of surface cubic phase-rich functional modified cemented carbide, and reduce the friction coefficient of the alloy material, has become a direction that needs to be focused on. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a surface cubic-rich phase functionally modified cemented carbide and a preparation method, aiming to solve the problems of low Vickers hardness, insufficient thermal conductivity, and poor wear resistance caused by excessively high friction coefficient in the existing surface cubic-rich phase modified cemented carbide.
[0006] The present invention performs yttrium doping treatment on tungsten carbide, uses boron-containing titanium carbide and cobalt-molybdenum composite powder together, and combines nitriding and sintering technology to promote the diffusion and penetration of nitrogen atoms, regulate the alloy microstructure, achieve the enrichment of cubic phase on the alloy surface, obtain surface cubic phase-rich functional modified cemented carbide, effectively improve the Vickers hardness and thermal conductivity of the cemented carbide material, and reduce the friction coefficient of the material; the surface layer of the modified cemented carbide material with a cubic phase-rich has a functional gradient layer, which can improve the bonding strength between the coating and the substrate of the tool material prepared by the modified cemented carbide, thereby increasing the service life of the tool material.
[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows: The first aspect of the present invention provides a method for preparing a surface cubic phase-rich functional modified cemented carbide, comprising the following steps: Step S1: by weight, 85-90 parts of yttrium-doped tungsten carbide, 4-6 parts of titanium carbide, 6-10 parts of cobalt powder and 1-2 parts of vanadium carbide are mixed evenly, placed in a ball mill for ball milling for 16-20 hours, and then vacuum dried for 2-3 hours, and after cooling, passed through a 200-mesh sieve to obtain a mixture; Step S2: wax-adding, grinding and granulating the mixture in a sealed state, and then pressing the mixture into a compact under a pressure of 100-200 MPa; Step S3: subjecting the compact to low-pressure and high-temperature sintering to obtain a surface-modified cubic phase functional cemented carbide; The preparation method of yttrium-doped tungsten carbide comprises: mixing 20-25 parts of glucose, 8-10 parts of ammonium metatungstate and 2-4 parts of yttrium chloride in parts by weight, adding 8-10 parts of deionized water and 8-10 parts of anhydrous ethanol and stirring for 50-60 minutes, and then keeping the mixture at 70-75°C for 8-10 hours to obtain a mixture, transferring the mixture to a box-type atmosphere furnace, heating it to 850-900°C at a rate of 5°C / min in a nitrogen atmosphere for 1-2 hours, naturally cooling it to room temperature, washing it, and drying it to obtain yttrium-doped tungsten carbide.
[0008] The yttrium element in yttrium-doped tungsten carbide can promote grain refinement of tungsten carbide, reduce the barrier effect of grain boundaries on thermal conductivity, and increase the number and continuity of thermal conduction paths. At the same time, yttrium doping can form a high thermal conductivity yttrium carbide phase, which has a high thermal conductivity coefficient and can be used as a thermal conduction channel in cemented carbide, significantly improving the overall thermal conductivity of the material.
[0009] As a preferred technical solution of the present invention, the titanium carbide is boron-containing titanium carbide. The preparation method of the boron-containing titanium carbide comprises: mixing 2 to 4 parts of two-dimensional titanium carbide powder and 12 to 15 parts of boric acid by weight, then transferring them to a horizontal tube furnace, heating them from room temperature to 190 to 200°C at a heating rate of 5°C / min for 4 to 6 hours, and cooling them naturally to obtain the boron-containing titanium carbide.
[0010] As a preferred technical solution of the present invention, the preparation method of the two-dimensional titanium carbide powder includes: adding 1.2 to 1.5 parts of lithium fluoride to 20 to 25 parts of a hydrochloric acid solution with a molar concentration of 8 mol / L, stirring for 15 to 20 minutes, then adding 2 to 4 parts of titanium carbide to react for 20 to 24 hours to obtain a mixed solution, centrifuging the mixed solution to obtain a precipitate, washing the precipitate 3 times with a hydrochloric acid solution with a molar concentration of 1 mol / L, then washing 8 times with deionized water, and vacuum drying for 18 to 20 hours to obtain a two-dimensional titanium carbide powder.
[0011] The boron-containing titanium carbide is firstly treated by acidification to form a two-dimensional titanium carbide powder, which is beneficial to promote the homogenization and flattening of the cemented carbide surface during the sintering process, thereby improving the surface smoothness; secondly, the introduction of the boron element can obtain a boride phase, which forms a self-lubricating film during the friction process, reducing the direct friction between the contact surfaces, and the combined effect reduces the friction coefficient of the cemented carbide.
[0012] As a preferred technical solution of the present invention, the cobalt powder is a cobalt-molybdenum composite powder. The preparation method of the cobalt-molybdenum composite powder comprises: placing 65-70 parts of cobalt and 25-30 parts of molybdenum powder in a crucible by weight, then transferring to a vacuum induction furnace for vacuum induction melting treatment, casting to form an atomized alloy ingot, and then subjecting the atomized alloy ingot to ultrasonic atomization treatment to obtain the cobalt-molybdenum composite powder.
[0013] Preferably, the conditions of the vacuum induction melting treatment include: vacuum degree of 3-4 Pa, temperature of 1500-1600° C., and time of 10-15 min.
[0014] Preferably, the conditions of the ultrasonic atomization treatment include: placing the atomized alloy ingot in an ultrasonic atomizer, evacuating to a vacuum degree of 4~5Pa, stopping the vacuuming when the temperature reaches 1400~1500°C, filling the furnace body with argon to normal pressure, and then adding silicon for smelting for 3~5min, the atomizing medium is argon, the atomizing pressure is 8~10MPa, and the alloy liquid flow rate is 4~5kg / min.
[0015] As a preferred technical solution of the present invention, the specific process of the low-pressure and high-temperature sintering treatment is: (1) Loading and vacuuming; (2) Heating to 800-850°C for dewaxing and pre-sintering, keeping warm for 1-3 hours; (3) Continue to raise the temperature to 1400~1450℃ for high temperature liquid phase sintering and keep it at this temperature for 0.5~1h; (4) Continue to raise the temperature to 1530~1550℃, then fill with nitrogen for pressurized nitriding sintering, control the pressure at 3~4MPa, and keep the temperature and pressurization for 2-3h; (5) After reducing the pressure, cool naturally and open the furnace to unload.
[0016] The second aspect of the present invention provides a surface cubic-rich phase functionally modified cemented carbide prepared by the method described in the first aspect.
[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention promotes the diffusion of nitrogen atoms in the sintering atmosphere to the alloy surface through nitriding treatment. Since the sample itself does not contain N element, N element diffuses from the high-content nitrogen in the sintering atmosphere to the alloy surface without N, reacts and migrates to the interior of the alloy. At the same time, Ti element migrates to the surface with relatively high N content, forming a cubic phase rich in Ti and N elements on the surface, thereby obtaining a cemented carbide with a surface rich in cubic phase. At the same time, nitrogen element can combine with boron element in boron-containing titanium carbide to form nitrogen boride. Nitrogen boride has high thermal conductivity and can also form a thermal conduction channel and optimize the microstructure to improve the overall thermal conductivity of the cemented carbide.
[0018] (2) The boron element in the boron-containing titanium carbide of the present invention can combine with the yttrium element in the yttrium-doped tungsten carbide to form a high hardness phase, while promoting the cemented carbide material to form a finer grain structure, providing sufficient strengthening points, thereby improving the hardness of the material.
[0019] (3) The boron-containing titanium carbide in the present invention can form boro-molybdenum compound with the cobalt-molybdenum composite powder. The boro-molybdenum compound can reduce defects and unevenness at the interface, improve surface roughness, and reduce the number of contact points, thereby reducing the friction coefficient and improving wear resistance.
[0020] (4) The cobalt-molybdenum composite powder of the present invention can promote the crystallization of tungsten carbide, improve the uniformity and density of the material, reduce defects and pores, and thus improve the hardness. At the same time, cobalt and molybdenum can improve the interface between tungsten carbide particles and bonding metal, reduce defects and unevenness at the interface, and improve the hardness of cemented carbide materials.
[0021] (5) The yttrium element in the yttrium-doped tungsten carbide of the present invention can promote the grain refinement of tungsten carbide, reduce the barrier effect of grain boundaries on thermal conductivity, and increase the number and continuity of thermal conduction paths. At the same time, yttrium doping can form a high thermal conductivity yttrium carbide phase, which has a high thermal conductivity coefficient and can serve as a thermal conduction channel in cemented carbide, significantly improving the overall thermal conductivity of the material.
[0022] (6) The boron-containing titanium carbide of the present invention is firstly treated by acidification to form a two-dimensional titanium carbide powder, which is beneficial to promote the homogenization and flattening of the cemented carbide surface during the sintering process, thereby improving the surface smoothness; secondly, the introduction of the boron element can obtain a boride phase, which forms a self-lubricating film during the friction process, reducing the direct friction between the contact surfaces, and the combined effect reduces the friction coefficient of the cemented carbide. DETAILED DESCRIPTION
[0023] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0024] The sources of some components in the embodiments and comparative examples are as follows: Commercially available tungsten carbide, brand FWC3A, purchased from GEM Co., Ltd.; Commercially available titanium carbide, product number 636967, was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; Commercially available cobalt powder, item number 0048, was purchased from Tianjin Zhuxin Metal Materials Co., Ltd.; Vanadium carbide, model XT-VC-02, purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.; Glucose, CAS No. 50-99-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Ammonium metatungstate, CAS No. 14311-52-5, purchased from Zhongshan Dixin Chemical Co., Ltd.; Yttrium chloride, CAS No. 10361-92-9, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Lithium fluoride, product number 669431, was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; Hydrochloric acid, CAS No. 7647-01-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Molybdenum powder, item number 0082, was purchased from Tianjin Zhuxin Metal Materials Co., Ltd.
[0025] Preparation of yttrium-doped tungsten carbide: In parts by weight, 25 parts of glucose, 10 parts of ammonium metatungstate and 4 parts of yttrium chloride are mixed evenly, 10 parts of deionized water and 10 parts of anhydrous ethanol are added and stirred for 60 minutes, and then the mixture is kept warm at 75°C for 8 hours to obtain a mixture, and the mixture is transferred to a box-type atmosphere furnace, and the temperature is increased to 900°C at a rate of 5°C / min in a nitrogen atmosphere for 1 hour, and then naturally cooled to room temperature, washed, and dried to obtain yttrium-doped tungsten carbide.
[0026] Preparation of boron-containing titanium carbide: (1) By weight, add 1.5 parts of lithium fluoride to 25 parts of 8 mol / L hydrochloric acid solution and stir for 20 minutes, then add 4 parts of titanium carbide and react for 24 hours to obtain a mixed solution, centrifuge the mixed solution to obtain a precipitate, wash the precipitate 3 times with 1 mol / L hydrochloric acid solution, then wash 8 times with deionized water, and vacuum dry for 20 hours to obtain a two-dimensional titanium carbide powder. (2) By weight, mix 4 parts of two-dimensional titanium carbide powder and 15 parts of boric acid, then transfer to a horizontal tube furnace, heat from room temperature to 200°C at a heating rate of 5°C / min for 4 hours, and cool naturally to obtain boron-containing titanium carbide.
[0027] Preparation of cobalt-molybdenum composite powder: 70 parts of cobalt and 30 parts of molybdenum powder are placed in a crucible by weight, and then transferred to a vacuum induction furnace for vacuum induction melting treatment (vacuum degree of 4Pa, temperature of 1600°C, time of 10min), cast to form an atomized alloy ingot, and then the atomized alloy ingot is placed in an ultrasonic atomizer, evacuated to a vacuum degree of 5Pa, and the vacuuming is stopped when the temperature reaches 1500°C. Argon is filled into the furnace body to normal pressure, and then silicon is added for smelting for 3min. The atomizing medium is argon, the atomizing pressure is 10MPa, and the alloy liquid flow rate is 5kg / min. After ultrasonic atomization treatment, the cobalt-molybdenum composite powder is obtained.
[0028] Example 1 This embodiment provides a method for preparing a surface cubic phase-rich functional modified cemented carbide, comprising the following steps: Step S1: 90 parts by weight of yttrium-doped tungsten carbide, 6 parts of boron-containing titanium carbide, 10 parts of cobalt-molybdenum composite powder and 2 parts of vanadium carbide are mixed evenly, placed in a ball mill for ball milling for 20 hours, and then vacuum dried for 3 hours, and after cooling, passed through a 200-mesh sieve to obtain a mixture; Step S2: wax-adding, grinding and granulating the mixture in a sealed state, and then pressing it into a compact under a pressure of 200 MPa; Step S3: subjecting the compact to low-pressure and high-temperature sintering to obtain a surface-modified cubic phase functional cemented carbide; The specific process of the low-pressure and high-temperature sintering treatment is: (1) Loading and vacuuming; (2) Heating to 850°C for dewaxing and pre-sintering, and keeping at this temperature for 1 hour; (3) Continue to raise the temperature to 1450°C for high-temperature liquid phase sintering and keep it at this temperature for 0.5h; (4) Continue to raise the temperature to 1550°C, then fill with nitrogen for pressurized nitriding sintering, control the pressure at 4 MPa, and keep the temperature and pressurization for 2 hours; (5) After reducing the pressure, cool naturally and open the furnace to unload.
[0029] Example 2 This embodiment provides a method for preparing a surface cubic phase-rich functional modified cemented carbide, comprising the following steps: Step S1: 85 parts by weight of yttrium-doped tungsten carbide, 4 parts of boron-containing titanium carbide, 6 parts of cobalt-molybdenum composite powder and 1 part of vanadium carbide are mixed evenly, placed in a ball mill for ball milling for 16 hours, and then vacuum dried for 2 hours, cooled and sieved through a 200-mesh sieve to obtain a mixture; Step S2: wax-blending, grinding and granulating the mixture in a sealed state, and then pressing it into a compact under a pressure of 100 MPa; Step S3: subjecting the compact to low-pressure and high-temperature sintering to obtain a surface-modified cubic phase functional cemented carbide; The specific process of the low-pressure and high-temperature sintering treatment is: (1) Loading and vacuuming; (2) Heating to 8000°C for dewaxing and pre-sintering, and keeping the temperature for 3 hours; (3) Continue to raise the temperature to 1400°C for high-temperature liquid phase sintering and keep it for 0.1h; (4) Continue to raise the temperature to 15300°C, then fill with nitrogen for pressurized nitriding sintering, control the pressure at 3 MPa, and keep the temperature and pressurization for 3 hours; (5) After reducing the pressure, cool naturally and open the furnace to unload.
[0030] Example 3 This embodiment provides a method for preparing a surface cubic phase-rich functional modified cemented carbide, comprising the following steps: Step S1: 88 parts of yttrium-doped tungsten carbide, 5 parts of boron-containing titanium carbide, 8 parts of cobalt-molybdenum composite powder and 1 part of vanadium carbide are mixed uniformly by weight, placed in a ball mill for ball milling for 18 hours, and then vacuum dried for 3 hours, and after cooling, passed through a 200-mesh sieve to obtain a mixture; Step S2: wax-adding, grinding and granulating the mixture in a sealed state, and then pressing it into a compact under a pressure of 150 MPa; Step S3: subjecting the compact to low-pressure and high-temperature sintering to obtain a surface-modified cubic phase functional cemented carbide; The specific process of the low-pressure and high-temperature sintering treatment is: (1) Loading and vacuuming; (2) Heating to 820°C for dewaxing and pre-sintering, and keeping at this temperature for 2 hours; (3) Continue to raise the temperature to 1430°C for high-temperature liquid phase sintering and keep it at this temperature for 1 hour; (4) Continue to raise the temperature to 1540°C, then fill with nitrogen for pressurized nitriding sintering, control the pressure at 4 MPa, and keep the temperature and pressurization for 2 hours; (5) After reducing the pressure, cool naturally and open the furnace to unload.
[0031] Comparative Example 1 This comparative example provides a method for preparing cemented carbide, which differs from Example 1 in that commercially available tungsten carbide is used instead of yttrium-doped tungsten carbide, commercially available titanium carbide is used instead of boron-containing titanium carbide, and commercially available cobalt powder is used instead of cobalt-molybdenum composite powder.
[0032] Comparative Example 2 This comparative example provides a method for preparing cemented carbide, which differs from comparative example 1 in that yttrium-doped tungsten carbide is used instead of commercially available tungsten carbide.
[0033] Comparative Example 3 This comparative example provides a method for preparing a cemented carbide, which differs from comparative example 1 in that boron-containing titanium carbide is used instead of commercially available titanium carbide.
[0034] Comparative Example 4 This comparative example provides a method for preparing cemented carbide, which differs from comparative example 1 in that cobalt-molybdenum composite powder is used instead of commercially available cobalt powder.
[0035] Comparative Example 5 This comparative example provides a method for preparing cemented carbide, which differs from Example 1 in that commercially available tungsten carbide is used instead of yttrium-doped tungsten carbide.
[0036] Comparative Example 6 This comparative example provides a method for preparing a cemented carbide, which differs from Example 1 in that commercially available titanium carbide is used instead of boron-containing titanium carbide.
[0037] Comparative Example 7 This comparative example provides a method for preparing cemented carbide, which differs from Example 1 in that commercially available cobalt powder is used instead of cobalt-molybdenum composite powder.
[0038] The performance of the cemented carbides provided in the above embodiments and comparative examples was tested, and the testing methods were as follows: the Vickers hardness was tested with reference to the requirements of "GB / T 7997-2014 Test method for Vickers hardness of cemented carbide"; the thermal conductivity was tested with reference to the requirements of "GB / T 10294-2008 Determination of steady-state thermal resistance and related properties of insulating materials - guarded hot plate method"; the friction coefficient was tested with reference to the requirements of "YB / T 4286-2012 Test method for friction coefficient of metal sheets and strips".
[0039] The above performance test data is shown in Table 1.
[0040] Table 1 Performance test results <![CDATA[Vickers hardness (HV 30 )]]> Thermal conductivity (W / mK) Friction coefficient Example 1 1286.8 152.7 0.22 Example 2 1282.3 150.8 0.24 Example 3 1284.5 151.6 0.23 Comparative Example 1 975.5 114.3 0.43 Comparative Example 2 975.8 128.4 0.41 Comparative Example 3 976.1 115.1 0.36 Comparative Example 4 1083.6 115.4 0.41 Comparative Example 5 1168.6 137.5 0.25 Comparative Example 6 1167.5 135.2 0.31 Comparative Example 7 1169.2 149.1 0.31 From the above content, it can be seen that the present invention obtains a surface-modified cemented carbide with a cubic phase-rich function (Example 1 to Example 3) by yttrium-doping tungsten carbide, using boron-containing titanium carbide and cobalt-molybdenum composite powder together, and combining the nitriding and sintering process. The Vickers hardness of the cemented carbide material is 1282.3~1286.8, the thermal conductivity is 150.8~152.7W / mK, and the friction coefficient is 0.22~0.24.
[0041] Compared with Example 1, commercially available tungsten carbide is used to replace yttrium-doped tungsten carbide, commercially available titanium carbide is used to replace boron-containing titanium carbide, and commercially available cobalt powder is used to replace cobalt-molybdenum composite powder, then the Vickers hardness decreases, the thermal conductivity decreases, and the friction coefficient increases (Comparative Example 1); Compared with Comparative Example 1, yttrium-doped tungsten carbide is used to replace commercial tungsten carbide, and the thermal conductivity increases (Comparative Example 2); Compared with Comparative Example 1, boron-containing titanium carbide is used to replace commercial titanium carbide, and the friction coefficient decreases (Comparative Example 3); Compared with Comparative Example 1, the use of When cobalt-molybdenum composite powder replaces commercially available cobalt powder, the Vickers hardness increases (Comparative Example 4); compared with Example 1, when commercially available tungsten carbide is used to replace yttrium-doped tungsten carbide, the Vickers hardness decreases and the thermal conductivity decreases (Comparative Example 5); compared with Example 1, when commercially available titanium carbide is used to replace boron-containing titanium carbide, the Vickers hardness decreases, the thermal conductivity decreases, and the friction coefficient increases (Comparative Example 6); compared with Example 1, when commercially available cobalt powder is used to replace cobalt-molybdenum composite powder, the Vickers hardness decreases and the friction coefficient increases (Comparative Example 7).
[0042] In summary, the present invention obtains a surface-modified cemented carbide with a cubic phase-rich function by yttrium-doping tungsten carbide, using boron-containing titanium carbide and cobalt-molybdenum composite powder together, and combining the nitriding and sintering process, and effectively improves the Vickers hardness and thermal conductivity of the cemented carbide material, while reducing the friction coefficient of the material.
[0043] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a surface-rich cubic phase functionally modified cemented carbide, characterized in that: The following steps are involved: Step S1: by weight, 85-90 parts of yttrium-doped tungsten carbide, 4-6 parts of titanium carbide, 6-10 parts of cobalt powder and 1-2 parts of vanadium carbide are mixed evenly, placed in a ball mill for ball milling for 16-20 hours, and then vacuum dried for 2-3 hours, and after cooling, passed through a 200-mesh sieve to obtain a mixture; Step S2: wax-adding, grinding and granulating the mixture in a sealed state, and then pressing the mixture into a compact under a pressure of 100-200 MPa; Step S3: subjecting the compact to low-pressure and high-temperature sintering to obtain a surface-modified cubic phase functional cemented carbide; The preparation method of yttrium-doped tungsten carbide comprises: mixing 20-25 parts of glucose, 8-10 parts of ammonium metatungstate and 2-4 parts of yttrium chloride in parts by weight, adding 8-10 parts of deionized water and 8-10 parts of anhydrous ethanol and stirring for 50-60 minutes, and then keeping the mixture at 70-75° C. for 8-10 hours to obtain a mixture, transferring the mixture to a box-type atmosphere furnace, heating the mixture to 850-900° C. at a rate of 5° C. / min in a nitrogen atmosphere for 1-2 hours, naturally cooling to room temperature, washing, and drying to obtain yttrium-doped tungsten carbide; The titanium carbide is boron-containing titanium carbide; The preparation method of boron-containing titanium carbide comprises: mixing 2 to 4 parts of two-dimensional titanium carbide powder and 12 to 15 parts of boric acid in parts by weight, then transferring the mixture to a horizontal tube furnace, heating the mixture from room temperature to 190 to 200° C. at a heating rate of 5° C. / min for 4 to 6 hours, and cooling the mixture naturally to obtain boron-containing titanium carbide; The preparation method of the two-dimensional titanium carbide powder comprises: adding 1.2 to 1.5 parts of lithium fluoride to 20 to 25 parts of a hydrochloric acid solution with a molar concentration of 8 mol / L, stirring for 15 to 20 minutes, then adding 2 to 4 parts of titanium carbide to react for 20 to 24 hours to obtain a mixed solution, centrifuging the mixed solution to obtain a precipitate, washing the precipitate with a hydrochloric acid solution with a molar concentration of 1 mol / L for 3 times, then washing with deionized water for 8 times, and vacuum drying for 18 to 20 hours to obtain a two-dimensional titanium carbide powder; The cobalt powder is a cobalt-molybdenum composite powder; The preparation method of the cobalt-molybdenum composite powder comprises: placing 65-70 parts of cobalt and 25-30 parts of molybdenum powder in a crucible, transferring the crucible to a vacuum induction furnace for vacuum induction melting treatment, casting to form an atomized alloy ingot, and then subjecting the atomized alloy ingot to ultrasonic atomization treatment to obtain the cobalt-molybdenum composite powder; The conditions of the vacuum induction melting treatment include: vacuum degree of 3-4 Pa, temperature of 1500-1600° C., and time of 10-15 min; The conditions of the ultrasonic atomization treatment include: placing the atomized alloy ingot in an ultrasonic atomizer, evacuating to a vacuum degree of 4-5 Pa, stopping the evacuation when the temperature reaches 1400-1500° C., filling the furnace body with argon gas to normal pressure, and then adding silicon for smelting for 3-5 minutes, the atomizing medium is argon gas, the atomizing pressure is 8-10 MPa, and the alloy liquid flow rate is 4-5 kg / min.
2. The method for preparing a surface-rich cubic phase functionally modified cemented carbide according to claim 1, characterized in that: The specific process of the low-pressure and high-temperature sintering treatment is: (1) Loading and vacuuming; (2) Heating to 800-850°C for dewaxing and pre-sintering, keeping warm for 1-3 hours; (3) Continue to raise the temperature to 1400~1450℃ for high temperature liquid phase sintering and keep it at this temperature for 0.5~1h; (4) Continue to raise the temperature to 1530~1550℃, then fill with nitrogen for pressurized nitriding sintering, control the pressure at 3~4MPa, and keep the temperature and pressurization for 2-3h; (5) After reducing the pressure, cool naturally and open the furnace to unload.
3. A surface-rich cubic phase functionally modified cemented carbide, characterized in that: Prepared according to the method according to any one of claims 1-2.
Citation Information
Patent Citations
Double-layer structure hard alloy with cubic phase-rich surface layer and preparation method thereof
CN111363963A
Rare earth-doped tungsten carbide composite powder, preparation method thereof, wear-resistant coating and preparation method of wear-resistant coating
CN112591753A
Three-dimensional layered boron-doped titanium carbide as well as preparation method and application thereof
CN113697811A
Preparation method of high-molybdenum high-silicon cobalt-based thermal spraying alloy powder
CN114570933A
Cited By
Hard alloy for complex rock stratum deep drilling and preparation method thereof
CN119553126A
Preparation method of metal surface hard welding layer
CN119681482A